Spy satellites and other intelligence technologies that changed history - Graham, Thomas 1933- (University of washington Press, 2007)
This book focuses instead on the central role that intelligence-collection systems play in promoting arms control and disarmament. Besides that, this books is based the failure of U.S. intelligence to prevent the terrorist attacks on September 11, 2001, and its overestimation of Iraq's weapons of mass destruction under Saddam Hussein.